Cytotoxicity and Genotoxicity of Panel of Single- and Multiwalled Carbon Nanotubes: In Vitro Effects on Normal Syrian Hamster Embryo and Immortalized V79 Hamster Lung Cells. (8th December 2014) - Darne, C.; Terzetti, F.; Coulais, C.; Fontana, C.; Binet, S.; Gaté, L.; Guichard, Y.
Abstract : Carbon nanotubes (CNTs) belong to a specific class of nanomaterials with unique properties. Because of their anticipated use in a wide range of industrial applications, their toxicity is of increasing concern. In order to determine whether specific physicochemical characteristics of CNTs are responsible for their toxicological effects, we investigated the cytotoxic and genotoxic effects of eight CNTs representative of each of the commonly encountered classes: single- SW-, double- DW-, and multiwalled (MW) CNTs, purified and raw. In addition, because most previous studies of CNT toxicity were conducted on immortalized cell lines, we decided to compare results obtained from V79 cells, an established cell line, with results from SHE (Syrian hamster embryo) cells, an easy-to-handle normal cell model. After 24 hours of treatment, MWCNTs were generally found to be more cytotoxic than SW- or DWCNTs. MWCNTs also provoked more genotoxic effects. No correlation could be found between CNT genotoxicity and metal impurities, length, surface area, or induction of cellular oxidative stress, but genotoxicity was seen to increase with CNT width. The toxicity observed for some CNTs leads us to suggest that they might also act by interfering with the cell cycle, but no significant differences were observed between normal and immortalized cells.